DRIVING FORCE CALCULATION FOR THE FRACTURE PROPAGATION OF DENSE PHASE CO2 TRANSMISSION PIPELINE - LIU LiYan; WU Xia (Jixie qiangdu)
The pure CO2 keeps in dense phase when the pressure is higher than the critical pressure and the temperature is lower than the critical temperature. The crack-driving force model for CO2 pipelines was established and solved based on Maxey’s fracture tip pressure-fracture propagation velocity correlation,the sonic-fracture velocity correlation and the BWRS equation of state. The proposed model was applied to simulate the crack-driving force of dense phase CO2 transmission pipelines at different temperatures and with different N2 concentrations. At the same operation temperatures,the crack-driving force decreases with increasing CO2 content in mixtures. When the CO2 content keeps a constant,the crack-driving force increases with increasing temperatures. In order to reduce the crack-driving force and the probability of fracture propagation,impurities in CO2 mixtures should be removed,and the pipeline should be operated at low temperatures as long as no phase transition occurs.